Technology Options for Public Safety and Disaster Relief Networks - Faruk, N.; Surajudeen-Bakinde, N. T.; Ayeni, A. A.; Bello, O. W.; Fadipe-Joseph, O. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2018)
The rise in global cases of emergencies as a result of man-made and natural disaster necessitates the need for a robust and reliable means of communication networks. The partial or complete, disruption of telecommunications infrastructure as a result of disaster has caused delays in emergency response and disaster relief efforts, leading to loss of lives and damage to properties. Although, modern telecommunications networks have reliability and resiliency to physical damage, however, the risks associated with communications failures remain a major issue as the severity of the damages may depend on the underlying technologies and architecture used. It is however important to also note that each technology option available for public safety network has its own unique characteristics. Some of these options are widely deployed for commercial purposes in Nigeria, while others are still in the developmental stages. This paper therefore outlines some of the existing, new and affordable technological options, available today that can be deployed for public safety and disaster telecommunications networks in Nigeria. Furthermore, the paper recommends that the national broadband network plan needs to be aligned to the current commercial deployments of the 4G Long Term Evolution (LTE) wireless services, this is to ensure that the pace is maintained with the changes in the technology and leveraging cost efficiencies for the public safety networks.